2018
DOI: 10.3889/oamjms.2018.221
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Kidney Diseases in Children Associated with Low Molecular Weight Proteinuria

Abstract: BACKGROUND:Proteinuria, in addition to haematuria, is the most important laboratory parameter in patients with nephro-urological diseases. Low molecular weight proteinuria (LMWP) is of particular importance because some diseases genetic and tubulointerstitial are diagnosed based on its presence.AIM:The purpose of this study is to describe the clinical features, the course and outcome of pediatric patients with a renal disease associated with LMWP.MATERIAL AND METHODS:This retrospective observational study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
2
1
Order By: Relevance
“…9 Previous reports showed that dipstick urinalysis in screening for proteinuria missed 8-56% of cases in a sample population, further highlighting a possible reason for the observed disparity. [20][21][22] The McNemar test of signi cance for the paired proportions shows 70% discordant result between UPr/UCr and dipstick proteinuria re ecting the higher false positive value for dipstick urinalysis at sub-nephrotic range proteinuria as previously reported. 3,6 The reason could be poor sensitivity of dipstick to proteinuria or its' inability to detect other forms of non-albumin proteinuria.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…9 Previous reports showed that dipstick urinalysis in screening for proteinuria missed 8-56% of cases in a sample population, further highlighting a possible reason for the observed disparity. [20][21][22] The McNemar test of signi cance for the paired proportions shows 70% discordant result between UPr/UCr and dipstick proteinuria re ecting the higher false positive value for dipstick urinalysis at sub-nephrotic range proteinuria as previously reported. 3,6 The reason could be poor sensitivity of dipstick to proteinuria or its' inability to detect other forms of non-albumin proteinuria.…”
Section: Discussionsupporting
confidence: 67%
“…3,6 The reason could be poor sensitivity of dipstick to proteinuria or its' inability to detect other forms of non-albumin proteinuria. 3,22 The 18% prevalence using UPr/Cr ≥ 0.2 found in this study is higher than the average prevalence of 12.2% (1.6-26.4%) in the reviewed studies in Table IIa. The few reported studies in Nigeria (Lagos-6.0% & Calabar-1.6%) and Turkey (7.2%) among apparently healthy children were far lower than the 18.0% observed in this study.…”
Section: Discussioncontrasting
confidence: 62%
“…The datasets for both refractive methods displayed a negative skew (manifest = −1.23, VASR = −1.46), which is to be anticipated in this particular population; most of the subjects were graduate students, who tend to have a higher prevalence of myopia (Figure 3). 11,12 Platykurtosis was also observed (manifest = 1.79, VASR = 2.85). Because of these factors, non-parametric analyses were performed using the Wilcoxon test.
Figure 2Box plot of results (Manifest vs VASR).
Figure 3Difference plot.
…”
Section: Resultsmentioning
confidence: 87%
“…Another problem is that urine protein electrophoresis has not been routinely used for screening for LMW proteinuria (10), thus, missing many opportunities to find tubular disease. LMW proteinuria can be found in a number of genetic tubulointerstitial diseases, such as nephronophthisis, Dent disease 1, Dent disease 2, Lowe syndrome, and cystinosis, in addition to the acquired diseases (11), which need next-generation sequencing (NGS) to be diagnosed. Therefore, insufficient awareness of genetic analysis is also an important factor that limits early diagnosis.…”
Section: Introductionmentioning
confidence: 99%